2020
DOI: 10.3382/ps/pez535
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of H-β zeolite as an ochratoxin binder for poultry

Abstract: Most of the cereal-based ingredients used in poultry feed are contaminated with ochratoxin-A (OTA). We have investigated H-β zeolite (HBZ) as a new OTA binder for poultry, along with widely used clay mineral-based product (CM), using in vitro and in vivo methods. In vitro binding experiment was carried out using a biphasic assay, consisting of adsorption at pH 3.2 and desorption at pH 6.8. High adsorption (>98%) with less desorption (<5%) was observed for HBZ, whereas CM showed high binding (>98%) and moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This exhibited no harmful effects such as immunosuppression, lymph proliferative responses to mitogen, or phagocytic action. Rajendran et al. (2020) , reported that H-β zeolite (1 kg/t of feed) as a toxin binder against OTA in poultry displayed better action.…”
Section: Mitigation Strategy For Prevention Of Otamentioning
confidence: 99%
“…This exhibited no harmful effects such as immunosuppression, lymph proliferative responses to mitogen, or phagocytic action. Rajendran et al. (2020) , reported that H-β zeolite (1 kg/t of feed) as a toxin binder against OTA in poultry displayed better action.…”
Section: Mitigation Strategy For Prevention Of Otamentioning
confidence: 99%
“…In this context, the use of adequate detoxification programs is highly recommended. The most well-known approach for the prevention of mycotoxins involves the use of inert adsorbents to bind mycotoxins, reducing their bioavailability in the gastrointestinal tract of animals [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, with 3 h of UV irradiation, 81–86% of OTA in feed can be degraded [ 18 ], but it requires extra equipment and is time-consuming. Chemical agents, such as ozone, ammonium, bisulfites, and alkaline hydrolysis, are commonly applied in detoxification [ 15 , 19 ]. However, its effectiveness varies and raises problems of chemical residues.…”
Section: Introductionmentioning
confidence: 99%